Rekam Medic Analysis Of The Relationship Of Completeness Of Secondary Diagnosis With The Increase Of INA-CBG'S Rates In RSUD Pandan Arang Boyolali - Ika Pratingkah Palupi; Astuti, Yuli (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
Background. Pandan Arang Boyolali Regional General Hospital is a type B referral hospital with an averageCompleteness in providing a diagnosis is something that must be considered by medical record personnel,completeness of diagnosis is very important in the field of clinical data management, billing of fees, along withother matters related to health care and services. INA-CBG's is an extension of the Indonesia Case base Groupwhich is an application used by hospitals in submitting claims with a package system based on the diseasesuffered, and then the hospital will receive payment according to the average cost spent by the diagnosis group.Knowing the relationship between completeness of secondary diagnosis and the increase in INA-CBG's rates atRSUD Pandan Arang Boyolali.The design of this study was observational with a cross sectional approach. The population in this study were allJKN patient medical record documents in the case of inpatients who were treated by more than one specialistdoctor at Pandan Arang Boyolali Hospital for the period January to March 2022 as many as 293 patients. TheIndonesian Journal of Health Information Management (IJHIM) Vol. x No. x (xxxx)| 2sampling technique is simple random sampling. Checklist instrument and documentation study. Data analysisusing chi square.The completeness of the secondary diagnosis in the medical records of inpatients at Pandan Arang BoyolaliHospital is complete for 53 patients (70.7%) The increase in rates for the medical records of inpatients at PandanArang Boyolali Hospital is for as many as 54 patients (72%) There are 12 record documents medical staff whoexperienced an increase after being completed and showed a positive difference of 78,557,700There is a relationship between the completeness of the secondary diagnosis and the increase in INA-CBG's ratesat RSUD Pandan Arang Boyolali